2015
DOI: 10.1091/mbc.e15-02-0085
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal degradation of preemptive quality control (pQC) substrates is mediated by an AIRAPL–p97 complex

Abstract: The preemptive quality control (pQC) pathway participates in the unfolded protein response regulating ER homeostasis, yet many components are not known. The role of p97 and its adaptor, AIRAPL, in proteasomal processing of pQC substrates is shown, and an insulin-processing mutant (R6C) is identified as a pQC substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 46 publications
(93 reference statements)
0
23
0
Order By: Relevance
“…While mutations in AIRAPL that eliminate binding to p97 do not impair its ability to bind Bag6 and ubiquitin ( Yun et al, 2008 ), we demonstrate that specific binding of AIRAPL to Lys48-linked ubiquitin chains is required for its interaction with both Bag6 and the proteasome ( Fig. 5 ) as well as pre-emptive quality control substrates that are designated for proteasomal degradation ( Braunstein et al, 2015 ). Therefore, the selective binding of AIRAPL to Lys48-linked poly-ubiquitin chains is not surprising as these chains are considered the canonical targeting signals for the proteasome ( Ciechanover and Stanhill, 2014 ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…While mutations in AIRAPL that eliminate binding to p97 do not impair its ability to bind Bag6 and ubiquitin ( Yun et al, 2008 ), we demonstrate that specific binding of AIRAPL to Lys48-linked ubiquitin chains is required for its interaction with both Bag6 and the proteasome ( Fig. 5 ) as well as pre-emptive quality control substrates that are designated for proteasomal degradation ( Braunstein et al, 2015 ). Therefore, the selective binding of AIRAPL to Lys48-linked poly-ubiquitin chains is not surprising as these chains are considered the canonical targeting signals for the proteasome ( Ciechanover and Stanhill, 2014 ).…”
Section: Discussionmentioning
confidence: 71%
“…AIRAPL is a p97 adaptor that has been demonstrated to bind Bag6 and the proteasome ( Glinka et al, 2013 , Yun et al, 2008 ) and is involved in the proteasomal processing of pre-emptive quality control substrates ( Braunstein et al, 2015 ). Functional impairment of AIRAPL homologues is linked to the acceleration of ageing and protein aggregation ( Yun et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mislocalized proteins are selectively degraded by the proteasome 34 . This type of cytoplasmic, non-ERAD degradation machinery for ER proteins has been defined as a preemptive quality control system, which can be fine-tuned to reduce the efficiency of translocation during ER stress in an SS-sequence-specific manner 6 8 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…We also recently reported that the signal sequence (SS)-truncated (and thus artificially mislocalized) single-pass TM protein IL-2Rα is captured by the UBQLN4/BAG6 complex in an unembedded TMD-dependent manner 4 . BAG6 is a hydrophobicity-oriented chaperone/holdase 18 24 that has been shown to be a receptor for tail-anchored (TA) protein biogenesis 25 31 and for targeted degradation of newly synthesized defective polypeptides with exposed hydrophobicity in the cytosol 2 , 7 , 19 , 20 , 32 34 . However, the critical functions of BAG6 in the elimination of the SS-uncleaved form of mislocalized TMD proteins have not been adequately proven and further experimental verification is awaited.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanism agrees with recent evidences that have demonstrated the implication of AIRAPL in pre-emptive quality control (PQC) pathway. 6 Accordingly, we propose that AIRAPL-dependent PQC activity promotes translocation of IGF1R nascent polypeptides out of the ER and their proteasome-mediated degradation. Although AIR-APL is unlikely to display E3-ligase activity, we have found that its overexpression is sufficient to promote IGF1R ubiquitination.…”
mentioning
confidence: 98%